2006
DOI: 10.1039/b605204e
|View full text |Cite
|
Sign up to set email alerts
|

Hexameric C-alkylpyrogallol[4]arene molecular capsules sustained by metal-ion coordination and hydrogen bonds

Abstract: Large multicomponent nanospheroid arrays consisting of six C-pentylpyrogallol[4]arene molecules and 12 Ga3+ metal-ions which in turn enclose 1150 A3 of chemical space are reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(48 citation statements)
references
References 21 publications
0
48
0
Order By: Relevance
“…From the work reviewed in this article, we have also shown that they are also useful templates for metal-organic analogues [116,[118][119][120][121]124,127]. The remarkable replacement of 48 hydrogen atoms in the hydrogen-bonded 'seam' with 24 copper Fig.…”
Section: Concluding Remarks and Future Prospectsmentioning
confidence: 87%
See 3 more Smart Citations
“…From the work reviewed in this article, we have also shown that they are also useful templates for metal-organic analogues [116,[118][119][120][121]124,127]. The remarkable replacement of 48 hydrogen atoms in the hydrogen-bonded 'seam' with 24 copper Fig.…”
Section: Concluding Remarks and Future Prospectsmentioning
confidence: 87%
“…When considering some of the largest supramolecular container assemblies formed to date [16,19,23,[47][48][49][50][68][69][70][84][85][86], hydrogen-bonded pyrogallol- [4]arene capsules (either dimeric or hexameric) are useful for the encapsulation of reasonably large non-solvent molecules, as identified by X-ray diffraction studies [96][97][98][99][100][101][102][103]116,[118][119][120]. From the work reviewed in this article, we have also shown that they are also useful templates for metal-organic analogues [116,[118][119][120][121]124,127].…”
Section: Concluding Remarks and Future Prospectsmentioning
confidence: 96%
See 2 more Smart Citations
“…The turn-on fluorescence signal can effectively discriminate ATP from ADP and adenosine 5′-monophosphate (AMP). Ga 3 þ ions were found to easily coordinate with oxygen atoms of hydroxyphenyl segments (Hastings et al, 2014;McKinlay et al, 2005McKinlay et al, , 2006. DHBO ligand is a typical fluorophore known for its excited state intramolecular proton transfer (ESIPT) characteristic (Xu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%